2011
DOI: 10.3201/eid1703.101550
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Outbreak Investigations in the United States, 2002–2008

Abstract: To understand circumstances of tuberculosis transmission that strain public health resources, we systematically reviewed Centers for Disease Control and Prevention (CDC) staff reports of US outbreaks in which CDC participated during 2002–2008 that involved >3 culture-confirmed tuberculosis cases linked by genotype and epidemiology. Twenty-seven outbreaks, representing 398 patients, were reviewed. Twenty-four of the 27 outbreaks involved primarily US-born patients; substance abuse was another predominant featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 25 publications
(79 reference statements)
1
55
0
1
Order By: Relevance
“…Each of the sublineages had specific mutations that, based on their SIFT values, suggested an impact on gene function. The strains from sublineage RD207 had a mutation in Rv0989c (grcC2), a diphosphate synthase required for cell wall biosynthesis (27). These strains also had a mutation in the gene Rv2959c, encoding a methyltransferase involved in the biosynthesis of phenolglycolipid, which is considered a virulence factor (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the sublineages had specific mutations that, based on their SIFT values, suggested an impact on gene function. The strains from sublineage RD207 had a mutation in Rv0989c (grcC2), a diphosphate synthase required for cell wall biosynthesis (27). These strains also had a mutation in the gene Rv2959c, encoding a methyltransferase involved in the biosynthesis of phenolglycolipid, which is considered a virulence factor (39).…”
Section: Discussionmentioning
confidence: 99%
“…Although some of these mutations may explain the pathological and immunological differences observed, there are a multitude of factors that can influence the transmission and pathogenic capabilities of a given isolate, such as host and environmental factors (5,20,27,38), HIV coinfection (42), and the concentration of organisms in environmental air (17). Until recently, the only bacterial factor considered was the presence of drug resistance; some studies have suggested that M. tuberculosis resistant to isoniazid is less transmissible (52) and less pathogenic than fully susceptible organisms (7,11), although an earlier study in our laboratory (33) investigating the virulence of multidrug-resistant isolates did not show much evidence of loss of virulence of these strains.…”
Section: Figmentioning
confidence: 99%
“…We believe this is because foreign-born children with TB who are living in the United States most likely acquired their infection before immigration to the United States, and if the source of their infection is still overseas it would not be captured in the NTSS. While index cases may not always be source cases, our findings are similar to those from studies that assessed risk factors for genotype clustering, 6 recent transmission 7 and involvement in outbreaks, 8 reinforcing the notion that index cases characterized by these risk factors may often be the source case for future cases. We found only one study that assessed characteristics associated with the generation of secondary cases using epidemiologic but not genotyping data.…”
mentioning
confidence: 99%
“…5,24 The index patient's prolonged infectious period, resulting primarily from treatment nonadherence but also a delay in seeking medical care, was the main factor that fueled this outbreak. Delayed diagnosis is a wellknown risk factor for TB transmission, 14,25 and it has previously contributed to at least two known TB outbreaks involving undocumented people. 26,27 Undocumented foreign-born people are more likely than documented people to delay seeking care for symptoms, 28 thereby prolonging the infectious period when TB can be transmitted to others.…”
Section: Discussionmentioning
confidence: 99%
“…13 To prevent further cases, exposed people with pending or incomplete TB evaluation and LTBI treatment were classified into high, medium, and low priority for follow-up based on the presence of TB risk factors, extent of exposure (i.e., intensity, duration, and frequency), and risk of developing TB disease. 13,14 Additional contacts identified during the outbreak investigation interviews and chart reviews were added to the database and prioritized for evaluation.…”
Section: Outbreak Investigationmentioning
confidence: 99%